(untitled) (Revista de Estudos da Linguagem, 2024)
The relations between Historical Linguistics and Corpus Linguistics are quite close and fruitful, especially from the 90’s, when the former gains renewed breath in Brazil, having in the edition of diachronic corpora one of the basic drivers for its progressive development. Under the sign of this intertwining between the two areas, this work, through content analysis, presents a case of reedition of a diachronic corpus, the Rio Grande do Norte official letters (1713-1950), and, through bibliographic research, proposes some reflections about the contact between these two fields of study in Brazil and the impacts, positive and negative, of the digital medium in this connection. The paper reveals how changes in research guidelines can justify a fruitful process of reedition and highlights both ethical risks and functional improvements to which these corpora are subject due to factors such as technology and the internet, proposing, in the end, a greater visibility of the issues raised in the study.